Consumption and Life-Styles A Short Introduction - Bögenhold, Dieter (Springer International Publishing, 2018)
This book takes an interdisciplinary approach to the world of consumption, covering different topics and including sociological, economic and marketing aspects. The term 'consumption' is vague and even in academic disciplines the term is used in a variety of ways. Consumption research asks how earnings and spending are related to each other. More generally, consumption research investigates how people, social classes or societies realize their consumption practices. The question of how consistent preference structures are due to changing empirical backgrounds of time, space and related culture is frequently asked. Which context variables (historical time, geographical framework, cultural background) specify the practice of consumption and in which way do attributes such as age, gender, class, occupation and life-style have their own impacts on the way in which consumption is realised? This book will be of interest to researchers working in economics, sociology, marketing, aesthetics and design, anthropology and communication studies. .